Drug resistance in pulmonary tuberculosis in new and previously treated cases: Experience from Turkey - Berna Komurcuoglu; Gunes Senol; Gunseli Balci; Enver Yalnız; Emel Ozden (Journal of Infection and Public Health, 2013)
Summary: The emergence of drug resistance is a major problem for tuberculosis (TB) control. The aim of this study was to determine the rates of resistance against TB drugs in patients with pulmonary tuberculosis (PTB). Data from 387 patients with active PTB between the years of 1999 and 2004 from the Research and Education Hospital for Chest Diseases and Chest Surgery were evaluated retrospectively. The patients were categorized as new, re-treatment, extrapulmonary and chronic cases. The study group consisted of 268 (69%) new, 57 (14.7%) re-treatment, 49 (12.6%) extrapulmonary and 13 (3.3%) chronic TB cases. The rates of resistance to isoniazid (INH), rifampicin (R), ethambutol (E) and streptomycin (S) were calculated separately for each group. The resistance to any of the drugs was 7.8% in the new cases, 58.5% in the re-treatment cases and 100% in the chronic cases. The multidrug-resistance (MDR)-TB rates were found to be 2.16%, 11.3% and 92.3% among the new, re-treatment and chronic cases, respectively. These data are important as they reflect the drug resistance rates during the pre-notification time period in western Turkey. Keywords: Drug resistance, Tuberculosis control programs, Tuberculosis